In his own words: Selections from the correspondence files of Casey A. Wood - Williams, Lauren (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2022)
As part of a themed print issue of the Papers of the Bibliographical Society of Canada dedicated to the life and work of Dr. Casey A. Wood, this article offers a selection of letters, written by Wood, from the ample correspondence preserved in his archival collections at the McGill Library in Montreal. The letters selected for this article express Wood’s philosophy of the ideal natural history research library; his approach to collection development, donor relations, and the book trade; and his ability to predict what future researchers would find valuable. Transcribed and annotated by the author, these letters illustrate the integral role Wood played in the development of the Emma Shearer Wood Library (ESW) of Ornithology and the Blacker Library of Zoology, and provide a glimpse into the mind and method of a voracious book collector.